2017
DOI: 10.1017/s1743923x17000204
|View full text |Cite
|
Sign up to set email alerts
|

President Park Geun-Hye of South Korea: A Woman President without Women?

Abstract: This article explores the first female president of South Korea, Park Geun-Hye, and her substantive representation of women. Though Park is one of many women executives from Asia taking the family route to power, her presidency still may lead to the implementation of women-friendly policies once elected. Park's government has expanded women-related policy areas first developed by previous progressive governments, but not consistently. Though mixed, her performance shows improvement over the previous conservati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The country is a patriarchal society for its level of development, which made Park's initial election significant for gender equality advocates. Despite her mixed record on advocating for women, some evidence shows women supported her in greater numbers in 2012 than they would for a typical conservative party candidate, suggesting that gender played a role in her election (Lee and Jalalzai 2017). Additionally, many advocates expressed concern that impeachment by an overwhelmingly male legislature would set South Korea's women's equality movement back 2 .…”
Section: Research Design and Contextmentioning
confidence: 99%
“…The country is a patriarchal society for its level of development, which made Park's initial election significant for gender equality advocates. Despite her mixed record on advocating for women, some evidence shows women supported her in greater numbers in 2012 than they would for a typical conservative party candidate, suggesting that gender played a role in her election (Lee and Jalalzai 2017). Additionally, many advocates expressed concern that impeachment by an overwhelmingly male legislature would set South Korea's women's equality movement back 2 .…”
Section: Research Design and Contextmentioning
confidence: 99%
“…Her term as the party chair deepened factionalism, rewarding or punishing party members for their loyalty, with women members often becoming the victims of such turf wars (Lee and Shin 2016, 364). Park did not propose any bills related to women during her legislative terms (Lee and Jalalzai 2017), even though conservative female legislators in Korea were proactively promoting women-friendly bills between 2000 and 2016 (Lee 2019b). While she highlighted her image as a selfless daughter continuing her father’s political legacy throughout her political career (Shin 2018), she emphasized the “first woman” aspect of her presidential candidacy only during the final month of her campaign (Lee 2017).…”
Section: Family Ties Gender and The Rise And Fall Of Park Geun-hyementioning
confidence: 99%
“…Two recent cases in northeast Asia suggest the pattern O'Brien et al identified may explain women's cabinet appointments better than the trend in Latin America. In South Korea, Park Geunhye, the country's first woman president, nominated fewer women cabinet members than her predecessors, contrary to her campaign pledge (Lee and Jalalzai, 2017). Abe Shinzo, the longest-serving former prime minister of Japan, promoted "Womenomics" to increase women's participation in the workforce (BBC News, 2014).…”
Section: Women Presidents and Cabinet Appointmentsmentioning
confidence: 99%